Real-time graphic visualization of filament band winding for fiber-reinforced cylindrical vessels. (July 2016) - Fu, Jianhui; Yun, Jaedeuk; Kim, Jeong-Suk; Jung, Yoongho
The filament winding method is widely used to manufacture lightweight, strong, composite products. To reduce winding time, the method of winding by filament band, which consists of several roving tows, is used. A computer numerical control winding machine is used with input path commands for precise winding operation. Before filament winding, users should verify by simulation that the input path is appropriate for the winding without any erroneous operation. Furthermore, prior to starting the winding operation, the usage length of each tow must to be checked because the manufacturing process stops unexpectedly if the tow on the creel runs out. In this work, we used the geodesic equation to generate a filament band surface and calculate the usage length of each tow. We also proposed a graphic display method to make the visual effect in accord with the real winding process. To verify the presented algorithm, a program for three-dimensional real-time graphic visualization of filament band winding process was developed.